Ultrasonic-based tensile force estimation for cylindrical rod at various temperature conditions. (15th August 2022) - Kwon, Ohjun; Sohn, Hoon; Lim, Hyung Jin
Highlights: Development of ultrasonic-based tensile force estimation technique. Investigation and compensation of the temperature effect on ultrasonic response. Tensile force estimation under varying temperature conditions. Application to the cylindrical rod specimen identical to the those used in a real suspension bridge. Abstract: This study presents the development of a tensile force estimation technique based on the ultrasonic bulk wave for cylindrical rod in a suspension bridge anchor system. Three piezoelectric macro fiber composites (MFC) transducers are installed on the surface of a cylindrical rod specimen for the generation and sensing of ultrasonic bulk waves. Ultrasonic responses are obtained at various tensile force levels and temperature conditions, and the relationship between the time lag of the ultrasonic response and the tensile force is established. In particular, the temperature effect on the tensile force estimation is theoretically derived and compensated for field applications. The originality of this study includes (1) theoretical derivation and investigation of the relationship between an applied tensile force level and the time lag of an ultrasonic response considering the variations of temperature, density, and elastic modulus, (2) development of a tensile force estimation and temperature compensation technique without temperature measurement, and (3) application to the tensile force estimation of the rod structure commonly used in a suspension bridge anchor system. The performance of the developed tensile force estimation technique was examined based on mock-up experiments of the rod structure of a real suspension bridge anchor system.